Ultraviolet-visible study on acid-base equilibria of aporphine alkaloids with antiplasmodial and antioxidant activities from Alseodaphne corneri and Dehaasia longipedicellata - Zahari, Azeana; Ablat, A.; Omer, N.; Nafiah, M.A.; Sivasothy, Y.; Mohamad, Jamaludin; Khan, M.N.; Awang, Khalijah (Nature Publishing Group, 2016)
The UV-vis spectra of isocorydine 1, norisocorydine 2 and boldine 3 were studied in 2% v/v acetonitrile, at constant ionic strength (0.1 M NaCl, 35 degree Celsius). The pKa values of isocorydine 1 and norisocorydine 2 were 11.75 and 12.07, respectively. Boldine 3 gave a pKa value of 9.16 and 10.44. All of the alkaloids 1-3 were stable at physiological pH; thereby all of them will not ionize, thus permitting the basic nitrogen to be protonated and accumulated within the acidic food vacuole of Plasmodium via pH trapping. Subsequently, acidic food vacuoles that have been neutralized by alkaloids would result in enhancement of the antiplasmodial activity. The alkaloids showed antiplasmodial activity against Plasmodium falciparum and antioxidant activities; DPPH radical scavenging, metal chelating and ferric reducing power. The antioxidant properties of the alkaloids under investigation revealed that in addition to the antiplasmodial activity, the alkaloids can also prevent oxidative damage. It can be prevented by binding free heme and neutralizing the electrons produced during the Plasmodium falciparum mediated haemoglobin destruction in the host. Slightly basic properties of the aforementioned alkaloids, along with their antioxidant activities, are advantageous in improving the suppression of malaria infection that cause less damage to the host.